Solution:
Given:
![2(10-a^2)+7a](https://tex.z-dn.net/?f=2%2810-a%5E2%29%2B7a)
when a = 4, substitute for a in the expression;
![\begin{gathered} 2(10-a^2)+7a=2(10-4^2)+7(4) \\ =2(10-16)+28 \\ =2(-6)+28 \\ =-12+28 \\ =16 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%202%2810-a%5E2%29%2B7a%3D2%2810-4%5E2%29%2B7%284%29%20%5C%5C%20%3D2%2810-16%29%2B28%20%5C%5C%20%3D2%28-6%29%2B28%20%5C%5C%20%3D-12%2B28%20%5C%5C%20%3D16%20%5Cend%7Bgathered%7D)
Therefore, if (a = 4), then
![2(10-a^2)+7a=16](https://tex.z-dn.net/?f=2%2810-a%5E2%29%2B7a%3D16)
Hence, the answer is 16.
Answer:
5(8-x)
Step-by-step explanation:
Fact using the GCF (Greatest Common Factor) of 40 and 5
Factors of 5:
1,5
Factors of 40:
1,2,4,5,8,10,20,40
The greatest factor they both have is 5
Factor by distributing out a 5
40-5x
5(8-x)
Answer: y=7+2x
Step-by-step explanation: Divide 5 by all. 5y/5=35/5 +10x/5.
Answer:
divide 5.125 by 1
Step-by-step explanation:
done bye
Answer:
(9-j)-3
Step-by-step explanation:
Let's start from the beginning and subtract j from 9. Because the word "from" is used, 9 will be the first number and j will be the second number.
We have 9-j
Now, we have to subtract 3 from the final answer. So, we have (9-j)-3